2016
DOI: 10.1021/acs.langmuir.5b03830
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Structural Differences in Galactocerebrosides on the Behavior of 2D Monolayers

Abstract: The molecular interactions of three biologically important galactocerebrosides have been studied in monolayers formed at the soft air/water interface as 2D model membranes. Highly surface-sensitive techniques as GIXD (grazing incidence X-ray diffraction), IRRAS (infrared reflection-absorption spectroscopy), and BAM (Brewster angle microscopy) have been used. The study reveals that small differences in the chemical structure have a relevant impact on the physical-chemical properties and intermolecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Ther esults ( Figure 5) clearly indicate that the OH group in the a-position does not influence its distribution. Thed ifferences of %l o for 1/3 and 5/7 are in the range of À0.03-0.03 and are not significant ( Monolayer experiments on galactosyl ceramide (GalCer), harboring either an a-hydroxylated or nonhydroxylated C 24:0 fatty acid on aL angmuir trough, suggest that the ahydroxylation does not change the area per lipid at 30 mN m À1 , [44] as urface pressure that reflects the packing density of bilayers. [45] Using 2 HNMR spectroscopy,M orrow and co-workers [41,46] also demonstrated that the order parameter of the fatty acids of GalCer embedded in aP OPC/Chol membrane and the orientation of the head group does not change considerably.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Ther esults ( Figure 5) clearly indicate that the OH group in the a-position does not influence its distribution. Thed ifferences of %l o for 1/3 and 5/7 are in the range of À0.03-0.03 and are not significant ( Monolayer experiments on galactosyl ceramide (GalCer), harboring either an a-hydroxylated or nonhydroxylated C 24:0 fatty acid on aL angmuir trough, suggest that the ahydroxylation does not change the area per lipid at 30 mN m À1 , [44] as urface pressure that reflects the packing density of bilayers. [45] Using 2 HNMR spectroscopy,M orrow and co-workers [41,46] also demonstrated that the order parameter of the fatty acids of GalCer embedded in aP OPC/Chol membrane and the orientation of the head group does not change considerably.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Monolayer experiments on galactosyl ceramide (GalCer), harboring either an α‐hydroxylated or nonhydroxylated C 24:0 fatty acid on a Langmuir trough, suggest that the α‐hydroxylation does not change the area per lipid at 30 mN m −1 , a surface pressure that reflects the packing density of bilayers . Using 2 H NMR spectroscopy, Morrow and co‐workers also demonstrated that the order parameter of the fatty acids of GalCer embedded in a POPC/Chol membrane and the orientation of the head group does not change considerably.…”
Section: Resultsmentioning
confidence: 99%
“…EE2 causes all the monolayers to have a reduced C −1 s ; the monolayers become more compressible with incorporation of EE2, especially for the charged DODAB and DPPG. At 30 mN.m −1 , which is the pressure believed to correspond to a real cell mem- brane [27,28], C −1 s decreased by 60% for DODAB, 57% for DPPG, 13% for DPPC, and 12% for StAc (from Fig. SI-2).…”
Section: Compressional Modulusmentioning
confidence: 94%